Decentralized Waste Governance and Local Implementation Challenges in Cambodia - Monyroth Thlork (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2026)
Abstract Solid waste management is an increasing environmental and governance challenge in Cambodia, where decentralization has transferred responsibilities to subnational administrations without consistently providing sufficient authority, funding, or technical capacity. Although previous studies identify weaknesses at national and municipal levels, district-level implementation of Sub-decree No. 113 remains insufficiently examined. This study investigates implementation challenges, local responses, and policy needs in Leuk Daek District, Kandal Province. Using a qualitative design, it analyses open-ended survey responses from 45 household residents and 45 market vendors, together with five key informant interviews involving three district administrators and two waste collectors in Prek Dach, Prek Tanlop, and Kampong Phnom Communes. The findings reveal that low collection fees, inadequate bins and disposal sites, irregular services, unclear institutional responsibilities, limited fiscal transfers, insufficient technical guidance, and weak local capacity constrain implementation. However, the formation of a district waste-management committee and training on disposal-site management, composting, and the 3Rs indicate emerging local progress. The study contributes district-level evidence that implementation gaps result from the interaction of unclear delegation, resource constraints, and weak service arrangements. It concludes that effective decentralization requires clearer mandates, aligned fiscal support, stronger coordination, viable collection systems, and sustained community and private-sector participation.